Antimicrobial evaluation, molecular docking, DFT analysis, and ADME studies of 3-Hydroxypyridin-4-one analogues - Hossein Sadeghpour; Sara Sadeghian; Fateme Zare; Mehdi Jamali; Narjes Moghtaderi Estahbanati; Kamiar Zomorodian; Zahra Zareshahrabadi; Razieh Sabet (Results in Chemistry, 2025)
A series of 3-hydroxypyridine-4-one analogues (5a–r, 6a–r) were evaluated for their antimicrobial activities against a broad panel of bacterial (E. coli, S. typhi, P. aeruginosa, B. subtilis, K. pneumoniae, and S. aureus) and fungal (C. albicans, A. niger, C. krusei, C. tropicalis, C. glabrata, C. parapsilosis, C. dublinensis, Cryptococcus neoformans, and Aspergillus flavus) species using the CLSI method. The studied compounds exhibited moderate to good antibacterial activity, with 5a–r generally outperforming 6a–r analogues. Notably, chlorine substitutions at the ortho and para positions of the phenyl ring (compounds 5d and 5o) significantly enhanced activity against E. coli (MIC = 32 μg/mL). Thiophene substitution (6j) improved potency against S. typhi and P. aeruginosa. Antifungal evaluation revealed that compounds bearing hydroxyl and isopropyl substituents, as well as thiophene and furan moieties, exhibited potent activity, with compound 5 l showing remarkable efficacy against C. krusei (MIC = 2 μg/mL) and compound 6b outperforming fluconazole against C. parapsilosis (MIC = 0.5 μg/mL). Molecular docking studies supported these findings by demonstrating strong binding affinities of potent compounds to bacterial Gyrase B and fungal sterol 14-alpha demethylase (CYP51). Density Functional Theory (DFT) calculations further elucidated the electronic properties correlating with reactivity and stability. These results highlight the critical role of Ar position substitutions in modulating antimicrobial activity and offer promising leads for the development of novel antibacterial and antifungal agents.